“A Greater Compass of Voice”: Elizabeth Taylor Greenfield and Mary Ann Shadd Cary Navigate Black Performance - Moriah, Kristin (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (Graduate Centre for the Study of Drama, University of Toronto, 2020)
The work of Elizabeth Taylor Greenfield and Mary Ann Shadd Cary demonstrate how racial solidarity between Black Canadians and African Americans was created through performance and surpassed national boundaries during the nineteenth century. Taylor Greenfield’s connection to Mary Ann Shadd Cary, the prominent feminist abolitionist, and the first Black woman to publish a newspaper in North America, reveals the centrality of peripatetic Black performance, and Black feminism, to the formation of Black Canada’s burgeoning community. Her reception in the Black press and her performance work shows how Taylor Greenfield’s performances knit together various ideas about race, gender, and nationhood of mid-nineteenth century Black North Americans. Although Taylor Greenfield has rarely been recognized for her role in discourses around race and citizenship in Canada during the mid-nineteenth century, she was an immensely influential figure for both abolitionists in the United States and Blacks in Canada. Taylor Greenfield’s performance at an event for Mary Ann Shadd Cary’s benefit testifies to the longstanding porosity of the Canadian/ US border for nineteenth century Black North Americans and their politicized use of Black women’s voices.